Cape Verde : Second Review Under the Policy Support Instrument and Request for Waivers of Nonobservance of Assessment Criteria: Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. (IMF Staff Country Reports; Country Report ;, 2012)
Cape Verde's authorities have tightened fiscal and monetary stances and have significantly reduced the gaps with program targets. Tax revenues held up well, but there were shortfalls in nontax revenue in addition to capital transfers. The spending execution was held below the budget. The authorities need to scale back the fiscal deficit in 2012 and in the medium term to ensure a sustainable fiscal position. Net domestic financing of the central government should decline to avoid crowding out private sector credit and lessen pressure on the balance of payments.